2021
DOI: 10.1186/s12871-021-01509-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of enhanced recovery after surgery protocol compliance on patients’ outcome in benign hysterectomy and establishment of a predictive nomogram model

Abstract: Background Enhanced recovery after surgery (ERAS) pathways have been shown to improve clinical outcomes after surgery. Considering the importance of patient experience for patients with benign surgery, this study evaluated whether improved compliance with ERAS protocol modified for gynecological surgery which recommended by the ERAS Society is associated with better clinical outcomes and patient experience, and to determine the influence of compliance with each ERAS element on patients’ outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…ERAS programs intended to improve surgical outcomes have been implemented across various hospital procedures across the world with positive outcomes. Low compliance rates with ERAS remain a challenge [ 46–48 ], and many studies have demonstrated that increasing compliance further improves outcomes [ 49 , 50 ]. Particularly for hospitals with a larger share of Medicare patients, where net difference is in many procedures at or near zero even for patients without complications, applying the protocols and technology enablers could have an immense impact on overall profitability.…”
Section: Discussionmentioning
confidence: 99%
“…ERAS programs intended to improve surgical outcomes have been implemented across various hospital procedures across the world with positive outcomes. Low compliance rates with ERAS remain a challenge [ 46–48 ], and many studies have demonstrated that increasing compliance further improves outcomes [ 49 , 50 ]. Particularly for hospitals with a larger share of Medicare patients, where net difference is in many procedures at or near zero even for patients without complications, applying the protocols and technology enablers could have an immense impact on overall profitability.…”
Section: Discussionmentioning
confidence: 99%
“…Results show that ERAS protocol for colorectal surgery allows faster recovery and also lower days of hospital stay in comparison with traditional protocol (17). There are increasing reports in the gynecological literature to improve outcomes (18,19). In a study (2012) Carter performed laparotomy for gynecological cancer in three hundred and eighty-nine patients and used fasttrack management (18).…”
Section: Discussionmentioning
confidence: 99%
“…The higher of the QoR-15 scores, the better of the quality of recovery after surgery (range is 0 to 150 points). 20 …”
Section: Methodsmentioning
confidence: 99%
“…The higher of the QoR-15 scores, the better of the quality of recovery after surgery (range is 0 to 150 points). 20 NRS pain scores were assessed for all patients at 2, 4, 6, 12 and 24 h after surgery (0 points: painless; 1-3 points: mild pain; 4-6 points: moderate pain; 7-10 points: severe pain). The quality of sleep was evaluated using a 10-point rating scale (0 = terrible sleep, 10 = excellent sleep).…”
Section: Primary and Secondary Outcomesmentioning
confidence: 99%